PREDIKSI DISTORSI HARMONISA PADA UTILITY LISTRIK PERUMAHAN YANG DISEBABKAN OLEH BEBAN NONLINIER MENGGUNAKAN STATISTIK PERBANDINGAN LINIER - Riza Widia; Herisajani Herisajani; Witrionanda Witrionanda (Elektron : Jurnal Ilmiah, 2009)
Loads of electricity utility consists of linear loads and non linear loads. The non linear loads for example TV, personal computer, VCD player, microwave and fluorescent lamp using electronics ballast. Loads with non linear characteristics become harmonic current source to electricity utility. Condition prediction used statistic linear comparison based on load power to THDi (Distortion of Harmonic Current). Measurement result using power quality analyzer and etap 4.0 (Fluke 43B) find typical THDi. The calculation and measurement result of PF and THD to loads of electricity utility show the differences less than 5%. However power factor formulation and distortions of harmonic current is valid